PENGARUH TEKNIK MIND MAPPING TERHADAP KETERAMPILAN MENULIS PUISI SISWA SEKOLAH DASAR - Dina Dahliana (Universitas Muhammadiyah Makassar, 2019)
Abstract. This research is motivated by the low writing skills of poetry. This is characterized by students' poetry writing skills that are not productive, still informative, students are still difficult to express their ideas, and are less attractive to students because they only use one technique. One learning technique that can improve poetry writing skills is mind mapping techniques. Mind mapping is also a learning technique to stimulate students' imagination in generating ideas, recording and summarizing using mind mapping. This study aims to examine the effect of Mind Mapping Technique on Poetry Writing Skills of students in elementary school.This study was an experimental study of Quasi Experimental Design with Nonequivalent Control Group Design. The population in this study were all fifth grade students of class V. Sampling is done by saturated sample technique (total sampling), namely VB class as an experimental class and VA class as a control class. The experimental class consisted of 34 students and the control class consisted of 36 students. The instrument used to determine the effect of mind mapping techniques is observation and documentation. The experimental class was treated by using mind mapping techniques in poetry writing skills while the control class without using mind mapping techniques.Based on the results of the pretest obtained the average value of the experimental class 60 and the average value of the control class 64.2. From the results of the comparison of the two sample classes, there was a difference in value of 3.7, so it can be concluded that there is no significant difference between the two pretest grades, meaning that the two classes have the same initial ability. Next, learning was conducted using mind mapping techniques in the experimental class and learning without mind mapping techniques in the control class. After learning is given then in both classes posttest is conducted. For the experimental class obtained an average value of 82 and for the control class obtained an average value of 77.5. From the results of testing hypotheses with a significant level of 0.05 obtained a significant value of 0,000 because sig. α, the hypothesis is accepted, so it can be concluded that there is an effect of using mind mapping techniques on students' poetry writing skills in elementary school. Keywords: Mind Mapping Techniques, Writing Skills, Poetry Abstrak. Penelitian ini dilatar belakangi oleh rendahnya keterampilan menulis puisi. Hal ini ditandai dengan keterampilan menulis puisi siswa belum bersifat produktif, masih bersifat teori informatif, siswa masih sulit untuk menuangkan ide-idenya, dan kurang menarik bagi siswa karena hanya menggunakan satu teknik (ceramah). Salah satu teknik pembelajaran yang dapat meningkatkan keterampilan menulis puisi adalah teknik mind mapping. Mind mapping juga merupakan salah satu teknik pembelajaran untuk merangsang imajinasi siswa dalam menghasilkan gagasan, mencatat dan meringkas menggunakan pemetaan pikiran. Penelitian ini bertujuan untuk meneliti Pengaruh Teknik Mind Mapping terhadap Keterampilan Menulis Puisi siswa di sekolah dasar.Penelitian ini adalah penelitian eksperimen jenis Quasi Experimental Design dengan rancangan Nonequivalent Control Group Design. Populasi dalam penelitian ini adalah seluruh siswa kelas V semester II. Pengambilan sampel dilakukan dengan teknik sampel jenuh (total sampling) yaitu kelas VB sebagai kelas eksperimen dan kelas VA sebagai kelas kontrol. Kelas eksperimen berjumlah 34 siswa dan kelas kontrol berjumlah 36 siswa. Instrumen yang digunakan untuk mengetahui pengaruh teknik mind mapping adalah observasi dan dokumentasi. Kelas eksperimen diberi perlakuan dengan menggunakan teknik mind mapping dalam keterampilan menulis puisi sedangkan kelas kontrol tanpa menggunakan teknik mind mapping.Berdasarkan hasil pretest diperoleh nilai rata-rata kelas eksperimen 60 dan nilai rata-rata kelas kontrol 64,2. Dari hasil perbandingan kedua kelas sampel tersebut diperoleh perbedaan nilai sebesar 3,7, maka dapat disimpulkan tidak terdapat perbedaan yang signifikan nilai pretest kedua kelas, artinya kedua kelas memiliki kemampuan awal yang sama. Selanjutnya dilakukan pembelajaran yang menggunakan teknik mind mapping pada kelas eksperimen dan pembelajaran tanpa teknik mind mapping pada kelas kontrol. Setelah pembelajaran diberikan kemudian pada kedua kelas dilakukan posttest. Untuk kelas ekperimen diperoleh nilai rata-rata 82 dan untuk kelas kontrol diperoleh nilai rata-rata 77,5. Dari hasil pengujian hipotesis dengan taraf signifikan 0,05 diperoleh nilai signifikan sebesar 0,000 karena sig. α maka hipotesis diterima, sehingga dapat disimpulkan bahwa terdapat pengaruh penggunaan teknik mind mapping terhadap keterampilan menulis puisi siswa di sekolah dasar. Kata Kunci : Teknik Mind Mapping, Keterampilan Menulis, Puisi